2013
DOI: 10.5901/ajis.2013.v2n9p284
|View full text |Cite
|
Sign up to set email alerts
|

Generational Effects of Handicraft Fair Trade Production: A Bangladesh Case Study

Abstract: Fair trade movements aim to respond to economic and social inequality and to support poor farmers and artisans in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To succeed in the HSC examinations, they received scaffolding instruction from the private tutors. Naka (2013 , p. 288) indicated that private tutoring is often crucial for Bangladeshi students to achieve good scores on the examination. Rahman et al (2019 , p. 24) pointed out that tutored students increased their mathematics, Bengali, and English scores by 3.2, 2.7, and 2.3 percentage points, respectively, when compared to non-tutored students.…”
Section: Resultsmentioning
confidence: 99%
“…To succeed in the HSC examinations, they received scaffolding instruction from the private tutors. Naka (2013 , p. 288) indicated that private tutoring is often crucial for Bangladeshi students to achieve good scores on the examination. Rahman et al (2019 , p. 24) pointed out that tutored students increased their mathematics, Bengali, and English scores by 3.2, 2.7, and 2.3 percentage points, respectively, when compared to non-tutored students.…”
Section: Resultsmentioning
confidence: 99%